Synopsis of the genus Mimothestus Pic with description of a new species from China (Coleoptera: Cerambycidae: Lamiinae) - Xie, Guang-Lin; Shi, Fu-Ming; Wang, Wen-Kai (Zootaxa, 2012)
The genus Mimothestus Pic, 1935 is reviewed. A new species, M. luteicornis, is described and illustrated, and two species are redescribed. A key to the four species is presented along with photographs of available species.